PEMAHAMAN EPISTEMOLOGIS CALON MAHASISWA MENGENAI ILMU-ILMU SOSIAL DAN ILMU-ILMU ALAM - Aditomo, Anindito (Jurnal Psikologi, 2017)
Epistemological understanding is an important part of college students’ intellectual development. The present study examines the structure of epistemological understanding on a sample of students in an Indonesian university. The study also compares epistemological understanding of the social and natural science disciplines. Participants were mostly female (58%), on average 17.9 years, and enrolled in either a social science (fashion design, law, and psychology; N = 575) or natural sciences study programme (engineering, pharmacy, and biology; N = 924). A Likert-type instrument was used to measure three dimensions of epistemological understanding regarding authority as a source of knowledge, the subjectivity of knowledge, and the changeability of knowledge. Eigen values and scree plot in the exploratory factor analysis indicate a four-factor solution. These factors referred to the three hypothesised dimensions, and one additional dimension reflecting beliefs related specifically to factual knowledge. Additional analyses show that knowledge in the social sciences are seen as more subjective and uncertain. Furthermore, while students generally trust epistemic authorities from both fields, the trust towards authority in the social sciences is associated with a belief that knowledge is subjective. The reverse pattern was found for the natural sciences. A possible explanation is that social science students recognised but were uncomfortable with the subjective nature of their discipline, and hence sought certainty from epistemic authorities.